Combating learning loss: How do students engage cognitively and affectively in online-based academic activities? - Fiki Alghadari; Audi Yundayani (Association for Scientific Computing Electrical and Engineering(ASCEE), 2022)
During the pandemic, education faces the problem of learning loss, however online academic activities can assist. This research addresses cognitive and affective online-academic engagement. This quantitative research of 208 students at private universities in Jakarta uses an observational technique and an explanatory design. This study analyzes the measurement and structural model of the relationship between factors from the emotional intelligence aspects and self-regulated learning in the flipped classroom context. The research findings indicate that students' cognitive and affective engagement is on track, as determined by their task persistence which can be established through effort and performance evaluation when completing the assignment. Effort and evaluation begin with self-awareness as a foundation for orientation and commitment. This study paves the way for further investigation of other findings that indicate the need to allocate and optimize time during pre-class activities while educating and encouraging students' persistence. Without tremendous effort and evaluation on the part of students, time on task for work can result in low-quality performance. These findings could drive teachers to construct engaging lesson plans by incorporating emotional intelligence and self-regulated learning prior class.